Perception of Convenience, Trust, Service Features, Risk and Interest in Using E-money among Denpasar City People - Putra, Ricky Utama Darma; Adi, I Nyoman Rasmen (International Journal of Science and Society, 2023)
The aim of this research was to find the influence of perceptions of convenience, trust, service features, risks and interest in using e-money on the people of Denpasar City. “The population used in this research is all e-money users in Denpasar City, the number of which cannot be ascertained because it will always change over time, with a sample size of 95. Data collection was carried out by distributing questionnaires using Google Form. The data analysis technique used is SEM-PLS. This research provides results that perceived ease of use has a positive and significant influence on interest in using. Perceived trust has a positive and significant influence on interest in using. Service features have no influence on interest in use. Risk perception has a positive and significant influence on intention to use.” Perception of convenience has a positive and significant influence on perception of risk. Perceptions of trust have a positive and significant influence on perceptions of risk. Service features have a positive and significant influence on risk perception. Perceived risk is an interventing variable that influences perceived ease of use on interest in using. Perceived risk is an interventing variable that influences perceived trust on interest in using. Perceived risk is not an intervening variable in the influence of service features on intention to use.